White blood cell count and long term mortality after non-ST elevation acute coronary syndrome treated with very early revascularisation. Issue 4 (1st April 2003) - Mueller, C; Neumann, F-J; Perruchoud, A P; Buettner, H J
Abstract : Objective: To evaluate the predictive value of white blood cell count (WBC) for short and long term mortality in patients with non-ST elevation acute coronary syndromes (NSTACS) treated with a very early invasive strategy. Design: Prospective cohort study in 1391 consecutive patients with NSTACS undergoing very early revascularisation. Patients were stratified according to quartiles of WBC determined on admission. Results: Kaplan-Meier survival analysis showed a cumulative three year survival of 93.8% in the first quartile of WBC (< 6800/mm 3 ), 94.4% in the second quartile (6800–8000/mm 3 ), 95.1% in the third quartile (8000–10000/mm 3 ), and 82.4% in the fourth quartile (> 10000/mm 3 ) at 36 months (p < 0.001 by log rank). Relative to patients in the three lower WBC quartiles, patients in the highest quartile were three times more likely to die during the hospitalisation (hazard ratio 3.2, 95% confidence interval (CI) 1.5 to 7.1; p = 0.003) and during long term follow up (hazard ratio 3.4, 95% CI 2.2 to 5.3; p < 0.001). By multivariate Cox regression analysis including baseline demographic, clinical, and angiographic covariables, WBC in the highest quartile remained a strong independent predictor of mortality (hazard ratio 3.3, 95% CI 1.9 to 5.6; p < 0.001). Conclusions: WBC is a strong independent predictor of short and long term mortality after NSTACS treated with very early revascularisation.